# y-2x=-5

3y-x=5

y = -5 + 2x

3y-x = 5

so 3*(-5 + 2x) - x = 5

-15 + 6x - x = 5

-15 + 5x = 5

x = 20/5

x = 4

y = -5 + 2 *4

y = 3

## To solve the given system of equations, you can use the method of substitution.

Step 1: Solve one of the equations for one variable in terms of the other variable. In this case, let's solve the first equation for y:

y - 2x = -5

y = -5 + 2x

Step 2: Substitute the expression for y in the second equation:

3y - x = 5

3(-5 + 2x) - x = 5

Step 3: Simplify and solve for x:

-15 + 6x - x = 5

-15 + 5x = 5

5x = 20

x = 20/5

x = 4

Step 4: Substitute the value of x back into one of the original equations to find y:

y = -5 + 2x

y = -5 + 2(4)

y = -5 + 8

y = 3

So the solution to the system of equations is x = 4 and y = 3.